Melaço de soja como substrato para a produção microbiana de (1→6)-β-D-glucana: avaliação do melaço bruto e do hidrolisado químico - Pecin, Silvia Barbosa (2018)
β-Glucans are macromolecules with innumerable biotechnological potentialities, and their production from agro-based by-products, such as soybean molasses, is an interesting alternative to reduce process costs. Thus, the objective of this work was to evaluate soybean molasses as substrate for the production of one (1®6)-β-D-glucan (lasiodiplodan) by the ascomycete Lasiodiplodia theobromae MMPI. Non-hydrolyzed and hydrolyzed soybean molasses were studied as a fermentation substrate. Initially, molasses were characterized as the content of glucose, fructose, sucrose, galactose, stachyose and raffinose, proximal composition (proteins, lipids, mineral residue and moisture), total soluble solids content (ºBrix), pH and content of total phenolic compounds. Crude soybean molasses were then clarified and subjected to chemical hydrolysis for saccharification of the oligosaccharides. Initial fermentations were conducted in agitated flasks to evaluate the need of nutritional supplementation of soybean molasses for lasiodiplodan production. Lasiodiplodan bioproduction assays using crude and hydrolyzed molasses were conducted in a submerged system in an orbital incubator at 150 rpm, 28 °C for 96 h. The lasiodiplodan samples obtained in both fermentations were characterized by Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TG, DTG, DTA) and scanning electron microscopy (SEM). Soybean molasses showed potential as a cultivation medium for both mycelial growth and lasiodiplodan production, no needing of nutritional supplementation. The results also indicated that there is no needing for previous hydrolysis of molasses for the lasiodiplodan production. The highest values of final production (0.41 g L-1), yield (0.021 g L-1) and volumetric productivity in lasiodiplodan (0.006 g L-1 h) were found in the non-hydrolyzed molasses assays. Thermal analysis indicated that both lasiodiplodan samples, presented three stages of mass-loss, the first stage occurred up to 150 °C, followed by two events between 250 °C and 525°C. FT-IR spectra by both lasiodiplodan samples shows typical signs of polysaccharides between 4000 and 400 cm-1 specially in 1060 cm-1 and 1600 cm-1, which correspond to the symmetrical stretching of C-O-C (characteristic group of sugars) and to the glucose ring vibration, respectively. SEM showed that lasiodiplodan samples have the appearance of thin films containing many filaments, heterogeneously arranged and superimposed over the material surface.